Community based maternal health fund: a case study from women's group initiative in Awbare woreda of Somali region of Ethiopia - Olusola, Oladeji; Bibilola, Oladeji; Abdifatah, Elmi Farah; Ayan, Mahdi Elmi (International Journal Of Community Medicine And Public Health, 2022)
Access to maternal and new born health services in most poor countries has been impeded by financial barriers and there has been increased attention for the mobilization of local resources to improve access to services. This study described the establishment, management and utilization of community based maternal health fund by indigenous women’s groups in a rural area of Somali region. The community-based fund was initiated and established by the women’s group as a result of financial constraints faced by pregnant women in accessing health services in the study area. The fund relied exclusively on the group’s monthly contribution and contribution by other members of the communities. The program is unique with the contributors not being beneficiaries of the fund and the management and operation of the fund was at group’s discretion. 754 pregnant women have benefitted from the fund since it was established in 2016 (403 supported during referral to the hospital; 284 provided with transport fare and basic household commodities after delivery and 67 hosted at the maternal waiting homes and provided with food and transport fare).The study demonstrates how community members are able to mobilize local resources to develop community solutions to identified local problems through active participation and commitment. Scaling up such innovative community initiated and managed funds that do not depend on external funding or beneficiary contributions has great potential to improve access to services and improve maternal health outcomes.